Tafsir Al-Quran Bi Al-Quran dalam Kitab Fushul Fi Ushul Tafsir Karya Musa’id Bin Sulaiman Al-Thayyar - Hari Fauji; Asep Ahmad Faturohman; Ade Jamarudin (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the application of the method of interpretation of the Qur'an using the Qur'an, the implications and objects of the verses of the Qur'an in the book of Fushul Fi Ushul Tafsir by Musaid Bin Sulaiman Al-Thayyar. The research method used is qualitative with descriptive analysis approach. Data were collected from primary sources, and secondary sources. The primary data used is the book of Fushul Fi Ushul Al-Tafsir while the secondary data is Ushul Al-Tafsir Wa Qawaiduhu and Qawaid Al-Tafsir Jam'an Wa Dirasah and other data that support this research. The results of this study are the analysis of interpretations that are in the Qur'an and also in the sunnah are part of Tafsir Bi Al-Riwayah, meaning that in order to explain God's purpose of interpreting the Qur'an based on the Qur'an or based on the Sunnah. al-Nabawiyyah. In the method of interpreting the Qur'an with the Qur'an, six tools were found to be able to interpret the verses of the Qur'an with the verses of the Qur'an, namely bayan al-Mujmal, taqyid al-Muthlaq, takhsis al-'Am, interpretation of al-Mafhum min verse bi verse ukhra, interpretation using lafaz with lafaz, interpretation using meaning with meaning, interpretation of uslub fi verse using uslub fi verse ukhra. And overall the methods of interpretation in the book of fushul fi ushul al-Tafsir there are six methods for interpreting the verses of the Qur'an. In general, what is often mentioned out of the six methods there are four methods, the six methods are the interpretation of the Qur'an with the Qur'an, the interpretation of the Qur'an with the Sunnah, the interpretation of the Qur'an with the words of the Companions, the interpretation of the Qur'an with the words of the Companions. Al-Qur'an with the words of tabi'in, interpretation of the Qur'an with al-Lughah, interpretation of the Qur'an with ratio and al-Ijtihad.